Excavation, analysis and interpretation of early Bronze Age barrows at Guiting Power, Gloucestershire - Marshall, Alistair (Archaeopress Archaeology, 2020)
Excavation, Analysis and Interpretation of Early Bronze Age Barrows at Guiting Power, Gloucestershire covers the full excavation, analysis and interpretation of two early Bronze Age round barrows at Guiting Power in the Cotswolds, a region where investigation and protection of such sites have been extremely poor, with many barrows unnecessarily lost to erosion, and with most existing excavation partial, and of low quality. One monument, Guiting Power 1, typical of many others in the region in terms of general form, was investigated to assess how far surviving evidence could be used to indicate original structure, as a basis for discussion of function as a funerary and ritual site. The project is paired with the full excavation of a larger round barrow, of similar date, nearby, at Guiting Power 3 in the valley below.